Key Drivers of Stock Price Movements: Financial and Economic Indicators in Unilever Indonesia (2014–2023) - Setiawati, Rini; Herlina, Listri (International Journal of Finance Research, 2024)
Multinational corporations are critical in ensuring financial market stability and boosting corporate performance, mainly through job creation and increased productivity. These contributions positively influence investor confidence and significantly impact stock market performance. As one of the leading multinational companies, PT Unilever contributes substantially to Indonesia's economic development. However, in recent years, PT Unilever has faced a notable decline in its stock prices. Such a decline can undermine investor trust, affecting the company’s investment strategies. For this reason, examining factors that influence stock price movements, including financial ratios and macroeconomic variables, becomes essential. This research investigates the influence of financial ratios and macroeconomic indicators on PT Unilever Indonesia Tbk's stock price fluctuations in 2014–2023. The variables analyzed include the Current Ratio (CR), Earnings Per Share (EPS), inflation, interest rates, and Gross Domestic Product (GDP). Using secondary data and a multiple linear regression approach, the study reveals that EPS and inflation positively and significantly impact stock prices. At the same time, interest rates and GDP exhibit a negative and significant effect. On the other hand, the CR variable does not significantly affect stock price movements